Implementasi Bat Algorithm dalam Optimasi Penempatan Femtocell - Nifty Fath; Eka Purwa Laksana; Rummi Sirait (Universitas Syiah Kuala, 2018)
Femtocell has been considered as an important technology to increase the cellular system capacity by bringing the base station closer to the user and shrinking the cell dimension. Basically, femtocell networks are deployed in indoor environment such as an office. Thus, femtocell placement problems are one of the important issues in planning the wireless networks, since the manual planning processes are not efficient. In this paper, the solution of femtocell placement problem in an indoor environment is solved by bat algorithm. Selecting the best position of the femtocell is the main objective so the capacity can be maximized. In a 100 trial study, the SNR can be optimized up to 34.89 dB. In conclusion, the bat algorithm is able to improve the SNR efficiently and effectively.